2022
DOI: 10.1007/s12264-022-00836-7
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid Biomarkers of Alzheimer’s Disease: Progress, Problems, and Perspectives

Abstract: Since the establishment of the biomarker-based A-T-N (Amyloid/Tau/Neurodegeneration) framework in Alzheimer’s disease (AD), the diagnosis of AD has become more precise, and cerebrospinal fluid tests and positron emission tomography examinations based on this framework have become widely accepted. However, the A-T-N framework does not encompass the whole spectrum of AD pathologies, and problems with invasiveness and high cost limit the application of the above diagnostic methods aimed at the central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 158 publications
0
18
0
Order By: Relevance
“…Even so, in this scheme, not all of the pathologies and related biomarkers are included. Therefore, Huang et al (2022) suggested adding an X to form the A-T-N-X framework, focusing on the CNS and periphery biomarkers associated with inflammation, systemic immunity, metabolism, and synaptic damage, neuroinflammation, glial cells. In the midto-long-term future, these frameworks should be validated in many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, in this scheme, not all of the pathologies and related biomarkers are included. Therefore, Huang et al (2022) suggested adding an X to form the A-T-N-X framework, focusing on the CNS and periphery biomarkers associated with inflammation, systemic immunity, metabolism, and synaptic damage, neuroinflammation, glial cells. In the midto-long-term future, these frameworks should be validated in many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the X category to the ATN framework allows for a better understanding of other pathologies and dynamic changes with the development of AD [ 67 ]. Huang et al proposed division by the X category for two subcategories, which could better reflect a whole spectrum of pathology in the central nervous system (CSN) and in periphery [ 68 ]. In , authors focused on biomarkers related to synaptic damage, glial cells, neuroinflammation, and immunity, whereas in , they focused on biomarkers associated with systemic immunity, inflammation, and metabolism [ 68 ].…”
Section: Diagnostic Scales For Interpretation Of Csf Biomarker Profilesmentioning
confidence: 99%
“…Huang et al proposed division by the X category for two subcategories, which could better reflect a whole spectrum of pathology in the central nervous system (CSN) and in periphery [ 68 ]. In , authors focused on biomarkers related to synaptic damage, glial cells, neuroinflammation, and immunity, whereas in , they focused on biomarkers associated with systemic immunity, inflammation, and metabolism [ 68 ]. The above-mentioned studies confirmed that AD is a very complex and multifactorial neurodegenerative disease.…”
Section: Diagnostic Scales For Interpretation Of Csf Biomarker Profilesmentioning
confidence: 99%
“…By the mid-21st century, the number of patients with dementia is predicted to reach 150 million, and the cost of treating, caring for, and managing these patients is estimated to be around 130 billion euros/year. , As a common type of dementia, Alzheimer’s disease (AD) is a progressive neurodegenerative disease with slow and insidious onset, and patients always go through three periods: preclinical, mild cognitive impairment, and eventual dementia . The clinical features of AD, such as memory and cognitive deterioration, aphasia, apraxia, and personality and behavioral changes, are characterized as irreversible symptoms .…”
Section: Introductionmentioning
confidence: 99%